Axisymmetric bis-tridentate Ir(iii) photoredox catalysts for anticancer phototherapy under hypoxia. Issue 21 (20th February 2023) - Wei, Li; Kushwaha, Rajesh; Dao, Anyi; Fan, Zhongxian; Banerjee, Samya; Huang, Huaiyi
Abstract : Axisymmetric bis-tridentate Ir(iii ) complex with strong synergetic type I/II photosensitization and photocatalytic were constructed for anticancer phototherapy under hypoxia and normoxia. Abstract : A novel axisymmetric bis-tridentate Ir(iii ) photocatalyst (Ir3 ) with synergetic type I/II photosensitization and photocatalytic activity was reported. Ir3 exhibited high photocytotoxicity toward drug-resistant cancer cells under normoxia and hypoxia. The photoactivated anticancer mechanism of Ir3 were investigated in detail. Overall, this new photo-redox catalyst can overcome hypoxia and drug resistance-related problems in clinical anticancer therapy.